Experimental investigation of reattachment behavior of turbulent lifted diffusion jet flames induced by repetitive DC electric pulse discharges with conditional PIV. Issue 4 (3rd April 2019) - Chang, T.-W.; Chao, Y.-C.; Cheng, T.-S.
ABSTRACT: Among the recently prevailing flame stabilization enhancement by electric field and plasma, repetitive DC electric pulse discharge is applied to a turbulent lifted diffusion jet flame to improve the reattachment in this study. The main objectove of this study is to characterize experimentally the stability and the reattachment behaviors of lifted flames under the electric pulse effect with a proposed electrode configuration. The effects of pulse repetition frequency (PRF) and voltage polarity on flame are investigated. The reattachment velocity increases by increasing PRF. The time history of flame base trace and absolute flame speed with positive-voltage-pulse are illustrated. The electric corona discharge is observed during upstream propagation process, and its role in flame acceleration is discussed. In addition, 2D-PIV measurement conditioned by high speed sequence images is conducted. Finally, the conditionally instantaneous flame propagation speed is enhanced and exceeds 3 times that of stoichiometric laminar flame speed, which leads to lifted flame reattachment.